Isolated genital annular lichen planus - Badri, Talel (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2011)
Annular lichen planus is a rarely reported variant of lichen planus (LP). Although genital lesions are frequent in patients with LP, isolated genital LPis rarely reported. We present a case of a 29-year- -old circumcised man with an asymptomatic annular lesion of the penis. Histopathological features were consistent with LP. Topical clobetasol was prescribed, with clinical improvement. It is important to consider annular LP among the possible diagnoses of individual annular genital lesions.
Keywords: dermatologija; lišaji; penis